The Relationship Between Snack Consumption and Dental Caries in Third and Fourth Grade Elementary School Students at SDN 064979 Medan 2024 - Lilis Novitarum; Vina Yolanda Sari Sigalingging; Sisilia Sisilia (Corona: Jurnal Ilmu Kesehatan Umum, Psikolog, Keperawatan dan Kebidanan, 2025)
The consumption of snacks sold outside of school environments contains a lot of sugar, such as artificial sweeteners. Environmental and social factors in schools, like unsupervised off-campus cafeterias, can influence children's food consumption patterns and oral health habits. This study aims to analyze the relationship between snack consumption and dental caries in school children. The research method used is correlation with a cross-sectional approach. A total sampling technique is applied to 80 respondents. Based on the research results, snack consumption is found to be 86.3% in the sufficient category, while 73.8% of respondents are categorized with dental caries. The Spearman rank correlation test resulted in p-value of 0.168 (p > 0.05), indicating that there is no significant relationship between snack consumption and dental caries among third and fourth-grade students. This study suggests that good oral hygiene and promoting healthy snacks should be targeted for preventing dental caries in children.